Polymorphism in the Plasmodium falciparum erythrocyte-binding ligand JESEBL/EBA-181 alters its receptor specificity - Mayer, D. C. Ghislaine (National Academy of Sciences, 2004)
The malaria parasite lives within erythrocytes and depends on the binding of parasite ligands to host cell surface receptors for invasion. The most virulent human malaria parasite, Plasmodium falciparum, uses multiple ligands, including EBA-175, BAEBL, and JESEBL of the Duffy-binding-like (DBL) family of erythrocyte-binding proteins, for invasion of human erythrocytes. Region II of these parasite ligands is the erythrocyte-binding domain. Previously, we had shown that polymorphism in region II of BAEBL leads to different erythrocyte-binding specificities. We have now identified and characterized the binding specificity of six JESEBL variants. We sequenced region II of JESEBL from 20 P. falciparum clones collected from various parts of the world where malaria is endemic. We observed eight JESEBL variants that contained amino acid polymorphisms at five positions among all clones. Seven of the eight variants could be connected by a single base change that led to an amino acid change. We investigated the functional significance of these polymorphisms by transiently expressing region II from six of JESEBL variants on the surface of Chinese hamster ovary cells. We observed four erythrocyte-binding patterns to enzyme-treated erythrocytes. Thus, P. falciparum DBL ligands JESEBL and BAEBL can recognize multiple receptors on the erythrocyte surface. In contrast to Plasmodium vivax, which has disappeared from West Africa because of the Duffy-negative blood group, P. falciparum may have been successful in endemic areas because it has mutated the ligands of the DBL family to create multiple pathways of invasion, thus making selection of refractory erythrocytes unlikely.